- TINJAUAN PERJANJIAN KREDIT BNI FLEKSI TANPA AGUNAN (ANALISIS KASUS PUTUSAN NOMOR 29/PDT.G.S/2020/PN BGL) : - - Kalisha Athallah Dyaniputri; Dinda Keumala (Faculty of Law, Universitas Trisakti, 2023)
Banks in providing credit do not always run smoothly, and defaults often occur, such as Decision Number 29/Pdt.G.S/2020/PN Bgl, debtors do not carry out their achievements in accordance with Credit Agreement Number: 2018/FLEKSI/096. In this research, the issues raised regarding the procedures for granting BNI Fleksi credit based on the Banking Law and the actions taken by BNI Bank if the debtor defaults are related to Decision Number 29/Pdt.G.S/2020/PN Bgl. This research uses a normative research method based on secondary data supported by interviews, data collected through literature study and interviews, as well as analyzed qualitatively and conclusions drawn using a deductive method. The results of this research are the procedures for granting BNI Fleksi credit, namely submitting a credit application, credit analysis, carrying out credit approval, and transferring accounts by bringing documents for disbursement. The efforts made by BNI Bank if the debtor is in arrears in payment are to remind them via SMS and telephone. If it is still not paid, BNI Bank will ask the customer's salary from the company where he works. In this decision, Bank BNI has given a summons 3 (three) times to the debtor, so that Bank BNI took the litigation route by filing a civil lawsuit with case number 29/Pdt.G.S/2020/PN.Bgl.